Multifocal Skeletal Tuberculosis Involving the Lumbar Spine and Iliac Bone, Mimicking a Malignant Bone Tumour: A Case Report - Gosal GS; Boparai A; Choudhary G; Kour R (Malaysian Orthopaedic Journal, 2012)
Multifocal osteoarticular tuberculosis is uncommon and accounts for approximately10% of all cases of osteoarticular tuberculosis. Concomitant vertebral and iliac bone tuberculosis has not been reported in the literature to date. We report one such case for its unusual clinical and radiological presentation, which had presentation more similar to a malignant bone tumour than an infection.